AXIOLOGICAL AZIMUTHS OF THE GLOBAL EDUCATIONAL POLICY - Bobrytska, Valentyna (Proceedings of National Aviation University (archive), 2016)
Purpose: As the initial point of methodological research the author defines understanding of the essence of value azimuths (orientation, benchmarks) in the formation of global education policy seen as a position on the decisive role of consolidation of efforts of supranational structures of the world, civil community in its global dimension, teachers’ associations and educational institutions of different levels in strengthening social and axiological ​​and personality-related and axiological factors of modernization of education as a strategic resource of socio-economic and cultural development of countries, an important lever of civilization development. Methods: In the article there has been used the method of terminological analysis to determine the essential content of the concepts of «value» and «ideal» in projections of development global education policy; the method of theoretical and comparative analysis to review the works of scientists on problems of shaping the global value-based measurements of educational policy. Results: The article presents implications made from the author’s conclusions regarding the content of the concepts of «value» and the «ideal» in projections of the global educational policy. It has been ascertained that the essential characteristics of the concept of «value» are as follows: 1) those are to satisfy the interests and needs of the individual; 2) specific individual reality whose essence lies in its positive significance; 3) «marker» of particular significance of things, processes, ideas for the life of the person; 4) what affects motivation and choice of modes of behavior of man. On the grounds that the term «ideal» denotes excellence, the perfect model, the ultimate goal of aspirations, activities, it has been found that the formation of modes of action, in particular, in the sphere of planning and implementing the global education policy, as far as the ideal is concerned, is a specific human form of vital activity, for it assumes the purposeful creating an image of the objective of the activity before its actual implementation. Based on generalisations of the scientific works of domestic and foreign scientists, scientific papers of the author, there has been defined, determined axiological azimuths, which, as it is seen by the author, are to be applied to evaluate compliance with the ethical principles in planning and implementing of the global education policy. There has been substantiated that humanistic and Gnostic values, values of social relationships, values, civic education, values and ideals of education in an open model of education, values of family education, health saving value should become some kind of benchmarks for the global educational policy. Discussion: The article is an attempt to define the basic values which a global educational policy is supposed to build on. The author elucidated the essential meaning of notions «value» and «ideal» in projections of development of a global educational policy. Significant attention is given the substantiation of values of global education policy, such as humanistic and Gnostic values, values of social relationships, values of civic education, values and ideals of education in an open model of education, values, family education, health saving value.